Anterior chain activation and high intensity gait training to improve walking in an adult with cerebral palsy: a case report - Brennan, Nicole; Hood, Ethan; Badman, Allyson (Physiotherapy theory and practice, 2025)
Adults living with Cerebral Palsy (CP) who are non-ambulatory are at increased risk for falls, contractures, reduced bone density, and pain. There is limited evidence for core strength training, anterior chain activation exercises, or high intensity gait training (HIGT) to improve gait function in adults with CP. The purpose of this case report is to describe the use of anterior chain muscle activation and HIGT to improve walking in a non-ambulatory adult male with quadriplegic CP. The participant was a 26 y.o. male living with spastic quadriplegic CP with a goal to cross the finish line of an adaptive triathlon while ambulating. The outpatient physiotherapy protocol emphasized anterior chain activation exercises and HIGT to improve strength, gait, and mobility at a frequency of 1-2 times a week for 8 months. The minimal detectable change of 19 points was achieved on the Function in Sitting Test (FIST). The original ambulation goal was exceeded to a maximum of 76 meters overground. The participant was able to walk across the finish line using a gait trainer while supervised at an adaptive triathlon. Focusing on anterior chain exercises and HIGT was effective to minimize extensor spasticity by strengthening body flexors allowing improved mobility and gait.